THE EFFECT OF FINANCIAL PERFORMANCE ON PROFIT CHANGES BEFORE TAX IN THE BANKING SUB-SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE - Clara Neltje Meini Rotinsulu; Samuel PD Anantadjaya; Christari Lois Palit; PA. Andiena Nindya Putri (SEAN Institute, 2023)
This study aims to determine the effect of independent variables, in the form of: Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR) and Non-Performing Financing (NPF) on Profit Changes at Commercial Banks in Indonesia for the 2015 - 2022 Period. The method used in this research is quantitative. A sample of 8 banks is used from a total population of 36 commercial banks in Indonesia. The results showed that the three independent variables had no effect on changes in commercial bank profits, either partially or simultaneously. So it is concluded that commercial banks in increasing profits do not need to focus on the three variables above